Modelling trends in solid and hazardous waste management - Sengupta, Debashish; Agrahari, Sudha (Springer, 2017)
This book explores state-of-art techniques based on methodological and modeling aspects of solid and hazardous waste management, specifically focusing on the recent trends in data acquisition and robust modeling of the results obtained. In addition to an in-depth description of the recent regulatory paradigm for solid waste disposal and revealing insights into solid waste management models, the book also addresses significant case history and remediation methodologies for sustainable development in emerging economies like India, China and Brazil. The main emphasis is on a suitable regulatory framework with site-specific baseline calibration and aimed at the robust modeling of contaminant transport and its remediation. This is based on instructive case history in various locations/regions worldwide. The focus on recent modeling and quantification methods is the backbone of the book. One of the major aspects discussed is the application of non-invasive methods for studies related to the Earth's interior, which are increasingly preferred over invasive techniques thanks to their economic utility, as well as robust techniques for the interpretation of geophysical data. The increasing demand for groundwater and energy resources, especially for rapidly emerging countries with large populations like India and China, has made it vital to derive safe utilization approaches for our resources, including suitable waste disposal and remediation methodologies that can be adopted for 'contaminated sites.'.